Analisis Empat Fondasi Berpikir Komputasi dalam Penyelesaian Soal Matematika - Surya Safii; Sunita Indira; Rekha Indah Sitanggang; Rosliana Siregar (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
This study aims to find out how students apply the four foundations of computational thinking in solving mathematics problems and whether students have applied computational thinking in solving mathematics problems. The research was conducted using an analytical approach to examine the results of solving mathematics problems. This approach involves collecting data from various sources, including tests, quizzes, or assignments given to research subjects. The collected data was then analyzed comprehensively to identify the use of four foundations of computational thinking in the process of solving mathematical problems. The results of this research are that students apply the four foundations of computational thinking. Decomposition by writing down what is known and looking for what is needed in the problem. Pattern recognition by understanding what is known and asking then using the right formula. Abstraction by writing formulas, ignoring what is not needed in the problem, and simplifying the answer. Algorithm by entering the required values into the formula then calculating them and solving the problem in the correct sequence of steps. Even though students make mistakes when solving mathematics problems, students can apply the four foundations of computational thinking.